Analysis of Indonesian Public Diplomacy Through Friends of Indonesia: Fellowship for Future Ambassadors Program 2018 - Achsin, Muhaimin Zulhair; Nadifa, Khairunnisa (Gorontalo Journal of Government and Political Studies, 2018)
The aim of this writing is to understand the Indonesian Public Diplomacy and how it works through one of the implemented program which is Friends of Indonesia: Fellowship for Future Ambassadors 2018 carried out under the Ministry of Foreign Affairs of Indonesia. In addressing to this subject, this writing will analyze the implementation and the impact of Public Diplomacy by the Ministry of Foreign Affairs of Indonesia with the concept of Mark Leonard’s three dimensions of Public Diplomacy, specifically in the dimension of Relationship Building in order to see the picture of Indonesian Public Diplomacy in the Friends of Indonesia program.